ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Maulida, Ayu (Jurnal Magister Manajemen, 2016)
This study aimed to analyze the differences in financial performance before and after mergers and acquisitions based on financial ratios : Current Ratio (CR), Quick Ratio (QR), Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Return On Assets (ROA), Return On Equity (ROE), Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), Fixed Assets Turnover (FATO), Total Assets Turnover (TATO), dan Earnings Per Share (EPS) at the companies listed on the Stock Exchange. This type of research is comparative , and sampling using purposive sampling. The type of data using quantitative data and data sources obtained from secondary data. The analysis technique used is the model for the Kolmogorov-Smirnov test for normality, and parametric test Paired Sample T Test to test hipoteisis. The results showed that there were significant differences between before and after mergers and acquisitions based on financial ratios Debt to Assets Ratio (DAR) in the comparative period of 2 years before and 2 years after puberty and acquisitions as well as comparison of 2 years before the 3 years after the mergers and acquisitions. The results also showed a significant difference based on financial ratios Debt to Equity Ratio (DER) at a ratio of 2-year period prior to 2 years after the mergers and acquisitions. While based on the ratio of Current Ratio (CR), Quick Ratio (QR), Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), fixed Assets Turnover (FATO), Total Assets Turnover (TATO), and Earnings Per Share (EPS), the results showed that there were no significant differences for all the study period. Keywords: Mergers and acquisitions, financial performance, quantitative, Paired Sample T Test